Challenges on the path toward sustainability in Europe : social responsibility and circular economy perspectives - Redek, Tjaša (Emerald Publishing Limited, 2020)
Challenges On the Path Toward Sustainability in Europe provides readers with guidance on sustainable actions at firm, consumer and institutional level. It studies the wide ranging challenges of implementing the sustainable development goals in Europe, while also addressing the challenges for key stakeholders in the economy. Vesna Zabkar and Tjaša Redek offer a theoretical and empirical approach to addressing sustainable development, providing rich data analysis at cross-country level, as well as practical examples from the European context. Its scientific outlook is based on extensive theoretical and empirical data analysis, however refraining from an extensively technical approach. Challenges On the Path Toward Sustainability in Europe is of direct relevance to both academics and practitioners seeking to expand their practical knowledge the subject as well as a richer theoretical background for analysing this field at the intersection of environmental and resource economics.